PENGARUH KEMUDAHAN PERBANKAN ELEKTRONIK TERHADAP KEPUASAN NASABAH PT BCA KANTOR CABANG HASYIM ASHARI - Boma Jonaldy Tanjung; Irwansyah Catur Nugraha (Lembaga Pengembangan Kinerja Dosen, 2022)
Electronic banking facilities are provided by PT BCA Tbk in order to provide convenience for customer in transacting. This will support customer satisfaction in transactions using BCA electronic banking products. Therefore, author want to know the extent of relationship between the ease of BCA electronic banking transactions on BCA customer satisfaction. By using the questionnaire research method, the variables used are independent variables which indicate the ease of electronic banking transactions and the dependent variable which indicates customer satisfaction. The results of data analysis with correlation test obtained correlation value of electronic banking convenience to customer satisfaction is 0.62. Meanwhile, customer satisfaction will increase positively and is influenced by the ease of electronic banking transactions of 0.40.